The Influence of Discipline and Work Motivation on Employee Productivity Improvement - Malik, Sahruddin; Aras Solong; Subhan Djaya; Khaerunnisa Sucipto (Cendekiawan Indonesia Timur, 2025)
This study aims to analyze the influence of discipline and work motivation on employee productivity at the Panakkukang District Office, Makassar City. Employee productivity is a crucial factor in achieving institutional goals, and both discipline and motivation play significant roles in enhancing work performance. This research employs a quantitative approach, using primary data collected through questionnaires and observations of employees. The analysis includes validity and reliability tests, as well as hypothesis testing using the F-test, T-test, multiple linear regression, and the coefficient of determination (R²). A total of 60 respondents were selected using the Slovin sampling technique. The findings reveal that the discipline variable has a significant positive effect on work productivity, as indicated by the t-test results (t-calculated = 7.132 > t-table = 2.002). Similarly, work motivation also significantly influences work productivity (t-calculated = 19.614 > t-table = 2.002). The F-test results show that discipline and work motivation simultaneously impact work productivity (F-calculated = 824.481 > F-table = 3.16). The multiple linear regression analysis further confirms the positive impact, with a coefficient of determination (R²) of 96.5%, meaning that the independent variables account for 96.5% of the variation in work productivity, while the remaining 3.5% is influenced by other factors not examined in this study.